The Development of A Chronic Diseases Clinic Model (Diabetes, Hypertension) in Primary Health Care Units, Mueang District, Sing Buri Province. - สาดตระกูลวัฒนา, วนิดา (Journal of Preventive Medicine Association of Thailand, 2018)
The purpose of this Participatory Action Research were to develop a chronic diseases clinic model (Diabetes, Hypertension) in primary health care units of Mueang District, Sing Buri province and To assessment the effectiveness of using The Development of A Chronic Diseases Clinic Model (Diabetes, Hypertension). The Study area were a total of 11 Primary Health Care Units Mueang District, Sing Buri Province. The research process were divided into 6 phases. Phases 1: Pre-Research phases. Phases 2: Situational analysis phases. Phases 3: Planning phase. Phases 4: Implementation phases. Phases 5: Evaluation phases. And Phases 6: Conclusion phases. Data collected by In-depth interview, observation, brainstorming, document analyzing, audio recording, and note taking. The data were analyzed by using descriptive analysis and qualitative data analyzed by content analysis. The research results of the study were as follows consisted of six main components: 1) The direction and policy are clear and consistent. 2) Management of appropriate information systems. 3) The system and service processes are optimized used was Seven Colors Traffic Pingpong balls. 4) Participation of community in co-operation 5) The staff at the primary care unit are confident. and 6) Community based self-care support is important and pushing for a community health plan. Performance based on model generated reduce congestion in general hospitals at 25%. Personnel services in primary care knowledge and understanding. and have the skills to work in clinics for chronic diseases in primary care. The result of the research showed that The Development of A Chronic Diseases Clinic Model (Diabetes, Hypertension) in Primary Health Care Units of Mueang District, Sing Buri province has the standard that Singburi Hospital can distribute to patients with diabetes and hypertension at primary care units. It helps to reduce congestion in patients with diabetes and hypertension in general hospitals.